The prognostic significance of PD-L1 expression in patients with glioma: A meta-analysis - Song Xue (Nature Portfolio, 2017)
Abstract A large number of studies have shown that programmed death-ligand 1 (PD-L1) is abnormally expressed in gliomas. However, the prognostic significance of PD-L1 expression in glioma patients remains unresolved. Accordingly, we conducted a meta-analysis to determine the prognostic role of high PD-L1 in patients with glioma. Electronic databases were searched to identify studies evaluating PD-L1 expression and overall survival (OS) in these patients. A total of 6 studies (published in 4 articles) that involved 1052 patients were included. Pooled results showed that high PD-L1 expression was associated with worse OS in glioma patients (HR = 1.30, 95% CI: 1.02–1.65, P = 0.032). Further subgroup analysis indicated that high PD-L1 expression in glioblastoma (GBM) was also associated with worse OS (HR = 1.40, 95% CI: 1.03–1.90, P = 0.030). Conversely, in index subgroup analysis, neither PD-L1 protein (HR = 1.43, 95% CI: 0.97–2.10, P = 0.068) nor gene (HR = 1.20, 95% CI: 0.83–1.74, P = 0.322) expression was significantly associated with OS. PD-L1 may represent a promising biomarker that predicts disease progression in patients with glioma or GBM. However, because of our limited sample size, further prospective or retrospective multi-centre, well-designed studies should be performed to verify this result.